Body Mass Index, Modified Bishop Score and Transvaginal Sonographic Measurement of the Cervical Length as Predictors of Successful Induction of Labour by Misoprostol (Medico Legal Update, 2020)
Introduction: All through the world, induction of labour fails in 20% of cases and thus cesarean sectionis performed. Obesity is a risk factor for undesired results of pregnancies. Although the Bishop score issimple and easy to apply, it is a subjective evaluation method and results may vary according to the clinicalexperience of the person applying it. Transvaginal cervical measurement can be more objective criterionin assessing the success of labor induction. We aimed to identify the proper characteristics of the pregnantwomen, which can go for successful induction of labour.Method: Induction of labor for 100 women using vaginal misoprostol was done following identification oftheir BMI, modified bishop score and transvaginal cervical length. All women were pregnant ?38 weeks,singleton, cephalic presentation, intact fetal membranes.Results: About 92 women had successful induction of labour (group 1) while the remaining eight womenhad failed induction (group 2). BMI did not show statistical significance however, the modified Bishop scoreand the transvaginal cervical length showed high statistical significance. Using the modified bishop score2 as a cutoff value showed sensitivity 89.1%, and specificity 62.5% while using the transvaginal cervicallength 2.65 as a cutoff value showed sensitivity 72.8% and specificity 100%.Conclusion: Induction of labour by vaginal misoprostol is very promising in term women providingidentification of their modified Bishop score and their transvaginal cervical length.